2023
DOI: 10.1002/adfm.202302311
|View full text |Cite
|
Sign up to set email alerts
|

Solid‐Like Slippery Coating with Highly Comprehensive Performance

Abstract: Many solar-power and wind-power devices in the world urgently demand self-cleaning and de-icing surfaces to ensure stable power generation. However, existing superhydrophobic surfaces and slippery liquid-infused porous surfaces with self-cleaning and de-icing functions are difficult to apply due to various defects. Herein, a novel solid-like slippery coating (SSC) is developed by constructing a smooth epoxy resin surface embedded with oil-stored silica nanoparticles. The SSC has excellent water-slippery capabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…Static contact angles (CAs) and roll-off angles (RAs) on the surfaces were measured by an optical measurement instrument (SL200KS, Kino, USA) using water droplets of ∼5 μL . Morphologies of different BETs were observed by a field-emission scanning electron microscope (SUPRA-55, Zeiss, Germany) and Zygo 9000 (NewView 9000, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Static contact angles (CAs) and roll-off angles (RAs) on the surfaces were measured by an optical measurement instrument (SL200KS, Kino, USA) using water droplets of ∼5 μL . Morphologies of different BETs were observed by a field-emission scanning electron microscope (SUPRA-55, Zeiss, Germany) and Zygo 9000 (NewView 9000, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Static contact angles (CAs) and roll-off angles (RAs) on the surfaces were measured by an optical measurement instrument (SL200KS, Kino, USA) using water droplets of ∼5 μL. 43 Morphologies of different BETs were observed by a field-emission scanning electron microscope (SUPRA-55, Zeiss, Germany) and Zygo 9000 (NewView 9000, USA). Chemical compositions on the surfaces of BETs were detected and analyzed by X-ray photoelectron spectroscopy (XPS, Thermo ESCALAB 250Xi, USA), while the C 1s peak at 284.6 eV was set as the reference of all binding energies.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, slippery liquid-infused porous surfaces (SLIPS) have been introduced as an antifouling alternative approach to superhydrophobic surfaces. It has been shown that SLIPS have many other excellent properties, such as anticorrosion, , anti-icing, , self-cleaning, , water mist capture, , and efficient condensation . Epstein et al reported SLIPS constructed on polytetrafluoroethylene (PTFE) films and evaluated their excellent antibacterial capability.…”
Section: Introductionmentioning
confidence: 99%
“…Inspiration has been gained from the groove structure of rice leaves, the wedge-shaped structure of bird beaks, and the lip of Nepenthes to create an anisotropic SLIPS on metal substrates that allows for continuous self-driving droplet transportation . While these SLIPS demonstrate excellent performance, the construction of rough porous structures during manufacturing is often complex. , Additionally, the use of silane-based molecules to achieve low surface energy modification is costly, and the use of fluorine-containing reagents is harmful to human health. , Moreover, the use of lubricants as liquids in SLIPS can lead to a decline in slippery performance over time as the lubricating oil is lost. To address these issues, researchers have proposed new approaches, such as coating a low-surface-energy paraffin layer or polymer on the substrate to create a slippery surface without any flowing lubricant. However, the practical application of these approaches is hindered by low water-slippery ability, low surface robustness, complex processes, and high cost. Therefore, there is a need for a facile, low-cost method to fabricate a solid-like slippery surface with excellent comprehensive performances, including superior water-slippery, antifouling, anti-icing, and fog collection abilities, surface robustness, and chemical stability.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Additionally, the use of silane-based molecules to achieve low surface energy modification is costly, and the use of fluorine-containing reagents is harmful to human health. 27,28 Moreover, the use of lubricants as liquids in SLIPS can lead to a decline in slippery performance over time as the lubricating oil is lost. To address these issues, researchers have proposed new approaches, such as coating a low-surface-energy paraffin layer or polymer on the substrate to create a slippery surface without any flowing lubricant.…”
Section: Introductionmentioning
confidence: 99%